“Because You’re Mine, I Walk the Line”? Marriage, Spousal Criminality, and Criminal Offending Over the Life Course - Schellen, Marieke (Journal of quantitative criminology, 2012)
Objectives This study is an analysis of the relationship between marriage and crime in a high-risk sample of Dutch men and women. Marriages are classified as to whether the spouse had been convicted of a crime prior to the marriage, in order to ascertain if one’s criminal career after marriage unfolds differently depending on the criminal history of one’s spouse. Methods Data are from the Criminal Career and Life-Course Study, a random sample of all individuals convicted of a criminal offense in the Netherlands in 1977 ( N = 4,615). Lifetime criminal histories for all subjects are constructed from age 12 to calendar year 2003. Official marriage records are also consulted, and the criminal history of all spouses are similarly constructed. Fixed-effects Poisson models are estimated to quantify the relationship between marriage, spousal criminality, and conviction frequency, controlling for age, parenthood, prior conviction, and prior incarceration. Results Among men, marriage reduces the frequency of criminal conviction, but only if the marriage is to a non-convicted spouse. Marriage to a convicted spouse, on the other hand, is indistinguishable from singlehood—it neither discourages nor promotes criminal behavior. Among women, marriage has a crime-reducing effect, regardless of the criminal history of the spouse. A set of preliminary follow-up analyses suggests further that men with more extensive criminal histories, and with more stable marriages, benefit in a more pronounced way from marriage to a non-convicted spouse. However, even unstable marriages to non-convicted spouses appear to reduce conviction frequency while they last. Conclusions Marriage is indeed a salient transition in the criminal career, but there are important differences depending on the characteristics of the offender (gender, criminal history), the characteristics of the spouse (criminal history), and the characteristics of the marriage (duration). The authors conclude that while marriage matters, it does not necessarily mean the end of a criminal career, and that processes of both partner selection and partner influence deserve close attention by marriage-crime researchers. Qualifications of the study’s findings include the use of conviction data from official sources, the use of a sample of men and women who were all convicted of a crime at some point in their lives, the study of legal marriage in the Netherlands, and the inability to measure potential mechanisms for the observed marriage effects.